The hare and the tortoise - Mackinnon, Mairi; Aesop Howarth, Daniel (Usborne London, 2007)
"Harry Hare loves running- and he loves talking about it too. When he suggests a race, nobody expects Tom Tortoise to take up the challenge."--Back cover